Experimental investigation on plant extract-induced biosynthesis of Nickel nanoparticles - Nimish Kumar; Anjali Singh; Vijay Devra (Next Nanotechnology)
Here, we describe the phytosynthesis of nickel nanoparticles (NiNPs) utilizing an extract from the leaves of Azadirachta indica as a reducing and capping agent. The optimal conditions for synthesizing stable NiNPs were pH 6.8, temperature 70°C, and 5 % leaf extract and [NiNO3.6H2O] = 1.0×10−3 mol dm−3. The X-ray diffraction (XRD) analysis revealed a face-centered cubic crystalline structure, and the Transmission Electron Microscope (TEM) and Scanning Electron Microscope (SEM) analyses verified a triangular form with particles ranging in size from 7 to 18 nm. The study examined the impact of reactant concentrations, reaction temperature, and solution pH on the nickel nanoparticle fabrication method. The following are the ideal parameters for synthesis: 5 % leaf extract, pH = 6.8, temperature = 70 °C, and [NiNO3.6H2O] = 1.0×10−3 mol dm−3. Plant biomolecules induce the reduction of nickel ions to NiNPs and function as a capping and stabilizing agent, as confirmed by the FTIR technique. The findings indicated that the synthesis of NiNPs from A. indica leaf extracts are safe technology and may have significant impacts on the industrial synthesis of metallic nanoparticles.